COLLINSITE IN HYDROTHERMAL ASSEMBLAGES RELATED TO CARBONATITES IN THE KOVDOR COMPLEX, NORTHWESTERN RUSSIA - Liferovich R.P.; Pakhomovsky Y.A.; Bogdanova A.N.; Balaganskaya E.G.; Laajoki K.V.O.; Gehör S.; Chukanov N.V. (My University, 2001)
Several generations of collinsite were formed during the hydrothermal alteration of phoscorite and dolomite carbonatite in the Kovdor alkaline-ultramafic complex, northwestern Russia. The collinsite at this locality shows isomorphic substitution of Sr fo r Ca at the A crystallographic site , which is atypical both for this species and for the entire fairfieldite group. The Sr content reaches 0.74 atoms per formula unit and shows an inverse correlation with Ca. Sr is found to account for no more than 37% of the total occupancy of the A site, a proportion that fits the Lewis acidity of interstitial cations, a value of 0.25 valence units (assuming a disordered distribution of Sr), which in turn matches the Lewis basicity of the structural unit in collinsite, the chain (Mg(PO4)2(H2O)2). The collinsite-bearing assemblages were formed by juvenile hydrothermal solutions derived from phoscorites and carbonatites that had been cooling in a tectonically active environment. Textural evidence and strontium isotopic character - istics show that the assemblages were superimposed upon the host rocks after the cataclasis of the dolomite carbonatite and selective leaching of its primary minerals. The Sr isotopic composition of collinsite and the associated hydrothermal phosphate s shows no contribution from any crustal component. Being confined to faults, the orthomagmatic hydrothermal solutions migrated upward and were not mixed with groundwater or crustal fluids in tectonic channels prior to deposition of the collinsite-bearing assemblages. The active fluid-rock interaction below 270 °C under wide variations in pH-Eh parameters, f(O2), f(S2), and rela- tively low f(CO2) did not homogenize the isotopic composition of Sr between the solutions and the affected carbonate rock.
Keywords: collinsite; strontian; hydrothermal; juvenile; phosphate; electron-microprobe analysis; carbonatite; Kovdor Complex; Russia